The Emergence of the Conserved AAA+ ATPases Pontin and Reptin on the Signaling Landscape - Rosenbaum, Jean (2013)
Pontin (also known as RUVBL1 and RVB1) and Reptin (also called RUVBL2 and RVB2) are related members of the large AAA+ (adenosine triphosphatase associated with diverse cellular activities) superfamily of conserved proteins. Various cellular functions depend on Pontin and Reptin, mostly because of their functions in the assembly of protein complexes that play a role in the regulation of cellular energetic metabolism, transcription, chromatin remodeling, and the DNA damage response. Little is known, though, about the interconnections between these multiple functions, how the relevant signaling pathways are regulated, whether the interconnections are affected in human disease, and whether components of these pathways are suitable targets for therapeutic intervention. The First International Workshop on Pontin (RUVBL1) and Reptin (RUVBL2), held between 16 and 19 October 2012, discussed the nature of the oligomeric organization of these proteins, their structures, their roles as partners in various protein complexes, and their involvement in cellular regulation, signaling, and pathophysiology, as well as their potential for therapeutic targeting. A major outcome of the meeting was a general consensus that most functions of Pontin and Reptin are related to their roles as chaperones or adaptor proteins that are important for the assembly and function of large signaling protein complexes.